1979
DOI: 10.1111/j.1834-7819.1979.tb02413.x
|View full text |Cite
|
Sign up to set email alerts
|

55 Nitinol wire: Force developed as a function of “elastic memory”

Abstract: Closing spaces is done either by translation of the edgewise brackets over an archwire or by the use of closing loops of some common design. This investigation suggests the concept of the further refinement of the "wire rubber band" as a means of closing spaces. Advantages of such a wire hypothetically would be to level the dentition, align the dentition, and condense spaces in the dentition with only one or two stretched nickel titanium wires having the proper temperature transition range (TTR). The temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The shape memory effect and the pseudoelasticity of NiTi alloys were developed by Buehler et al [1] in the early 1960s and introduced into orthodontic applications by Andreasen et al [2][3][4][5]. These properties are related to a thermoelastic martensitic transformation (austenite ~ martensite) which can be produced by cooling or may be stress induced.…”
Section: Introductionmentioning
confidence: 99%
“…The shape memory effect and the pseudoelasticity of NiTi alloys were developed by Buehler et al [1] in the early 1960s and introduced into orthodontic applications by Andreasen et al [2][3][4][5]. These properties are related to a thermoelastic martensitic transformation (austenite ~ martensite) which can be produced by cooling or may be stress induced.…”
Section: Introductionmentioning
confidence: 99%
“…In additional publications, Andreasen and his colleagues described the force delivery and temperature dependence for nitinol wires. [4][5][6] Subsequently, Burstone et al 7 and Miura et al 8 introduced the Chinese and Japanese NiTi wires, respectively, to the specialty. These wires, now marketed as Ni-Ti (Ormco/Sybron, Glendora, Calif.) and Sentinol or Sentalloy (GAC International, Central Islip, N.Y.), displayed superelastic characteristics, where the deactivation plot contains an extended region of largely constant bending moment or tensile stress.…”
mentioning
confidence: 99%
“…16,33 Our SEM images of the three types of archwire showed that NiTi wire and TMA wire were rougher than the stainless steel wire. However, further experimental measurements, such as using atomic force microscope or specular reflectance, are needed to obtain quantitative surface roughness data.…”
Section: Discussionmentioning
confidence: 87%